Advanced sol–gel process for efficient heterogeneous ring-closing metathesis - Shiran Aharon (Nature Portfolio, 2021)
Abstract Olefin metathesis, a powerful synthetic method with numerous practical applications, can be improved by developing heterogeneous catalysts that can be recycled. In this study, a single-stage process for the entrapment of ruthenium-based catalysts was developed by the sol–gel process. System effectiveness was quantified by measuring the conversion of the ring-closing metathesis reaction of the substrate diethyl diallylmalonate and the leakage of the catalysts from the matrix. The results indicate that the nature of the precursor affects pore size and catalyst activity. Moreover, matrices prepared with tetraethoxysilane at an alkaline pH exhibit a better reaction rate than in the homogenous system under certain reaction conditions. To the best of our knowledge, this is the first study to present a one-step process that is simpler and faster than the methods reported in the literature for catalyst entrapment by the sol–gel process under standard conditions.